Studi Sosial Pengaruh Menonton Berlebihan dan Kesepian Terhadap Interaksi Parasosial - Unga, Andi Adhari Fargianas; Prastika, Netty Dyan (Jayapangus Press, 2024)
Tendency limits need to pay attention to the quality of life so that everything is not excessive, a culture of healthy living must continue to be built and implemented, good living habits need to be managed regularly so that the lifestyle persists for each individual, such as watching excessively and feeling lonely in the life of parasocial interaction. The aim of this research is to determine the effect of excessive viewing and loneliness on parasocial interactions. This research method uses a quantitative approach. The subjects of this research were 76 students who were students of the Faculty of Pharmacy and Clinical Pharmacy. The data collection method used was a Likert scale, namely a scale of excessive viewing, loneliness, and a scale of parasocial interaction. The results of the research show that: (1) there is a significant influence on excessive watching and loneliness on parasocial interactions among students Pharmacy with a calculated F value = 14.197; (2) there is a negative and significant influence effect of excessive watching on parasocial interactions with beta coefficient (β) = -0.116, t = -0.976; (3) there is a positive and significant influence of loneliness on parasocial interactions with a beta coefficient (β) = 0.612, t = 5.162.